A Study on the Relationship Between Emotional Intelligence and Willingness to Communicate in Second Language among English Majors - Geng, Lihong; Lee, Seungjin (Journal of Educational Research and Policies, 2024)
Based on a questionnaire survey of 549 English majors in China, this study examined the emotional intelligence and willingness to communicate in second language of English majors and the relationship between them through descriptive statistics, correlation analysis, and regression analysis. The results show that the overall levels of emotional intelligence and willingness to communicate in second language of English majors are in the middle to upper level, and emotional intelligence has a significant predictive effect on willingness to communicate in second language. The study suggests that the emotional intelligence factor sheds some light on the teaching of oral English for English majors. The findings of this study provide theoretical basis and empirical support for teachers to better stimulate English majors’ oral communicative willingness.